High-dose therapy and autologous stem cell transplantation for extra-nodal NK/T lymphoma in patients from the Western hemisphere: a study from the European Society for Blood and Marrow Transplantation. Issue 12 (2nd December 2015) - Fox, Christopher P.; Boumendil, Ariane; Schmitz, Norbert; Finel, Herve; Luan, Jian J.; Sucak, Gülsan; Blaise, Didier; Finke, Jürgen; Pflüger, Karl-Heinz; Veelken, Hendrik; Gorin, Norbert -Claude; Poiré, Xavier; et al.
Abstract : Extra-nodal NK/T lymphoma (ENKTL) is rare and more frequently encountered in East Asia. The role of high-dose therapy and autologous stem cell transplantation (HDT-ASCT) for ENKTL is unclear. Twenty-eight evaluable patients who had undergone HDT-ASCT in Europe from 2000–2009 were studied. The median age was 47 years and patients had received a median of two lines of prior therapy. Some 57% of patients were not in complete remission or beyond first complete remission at HDT-ASCT. The 1-year non-relapse mortality (NRM) was 11%; 2-year progression-free survival (PFS) and overall survival (OS) rates were 41% and 52%, respectively. Notably, the 2-year PFS and OS for those with stage III/IV disease were 33% and 40%, respectively, with no relapses beyond 1-year post-HDT-ASCT. This is the largest analysis of HDT-ASCT for patients with ENKTL reported from the Western hemisphere. Survival is comparable to East Asian cohorts and outcomes are encouraging for patients with advanced disease.